Numerical and outdoor real time experimental investigation of performance of PCM based PVT system - Fayaz, H.; Rahim, Nasrudin Abd; Hasanuzzaman, Md.; Rivai, Ahmad; Nasrin, Rehena (Elsevier, 2019)
Photovoltaic power generation is a suitable option to counter depleting and environmentally hazardous fossil fuels. However, increased cell temperature of the photovoltaic module reduces the electrical performance. Therefore, for enhancing the electrical performance as well as to obtain the useful thermal, a combined photovoltaic thermal system is suitable technology. Furthermore, the addition of phase change materials into photovoltaic thermal systems adds more dual benefits in terms of cooling of PV cell as well as heat storage. Hence, there are still issues to transfer heat from the system efficiently, which cause lower performance of PVT and PVT-PCM systems. In this paper, the aluminium material of thermal collector is used by introducing a novel design to enhance heat transfer performance, which is assembled in PVT and PVT-PCM systems. Experimental validation is carried out for the 3D FEM-based numerical analysis with COMSOL Multiphysics® at 200 W/m2 to 1000 W/m2 varying irradiation levels while keeping mass flow rate fixed at 0.5LPM and inlet water temperature at 32 °C. The experiment is carried out at outdoor free weather conditions with passive cooling of the module by an overhead water tank scheme. A good agreement in numerical and experimental results is achieved through experimental validation. Cell temperature reduction of 12.6 °C and 10.3 °C is achieved from the PV module in case of the PVT-PCM system. The highest value of the electrical efficiency achieved is 13.72 13.56% for PV and 13.85 and 13.74% for PVT numerically and experimentally respectively. Similarly, for PVT-PCM, electrical efficiency is achieved as 13.98 and 13.87% numerically and experimentally respectively. In the case of the PVT system, electrical performance is improved as 6.2 and 4.8% and for PVT-PCM, it is improved as 7.2 and 7.6% for numerically and experimentally respectively.